Characterization of the agriculture-livestock-environment integration system (sia2e) in the Maradi region along the north-center-south gradient - Ibrahim Kasso A. Rahamane; Mahamane Larwanou; Massaoudou Moussa; Baragé Moussa; Zounon Christian Serge Félix (Discover Agriculture)
Abstract In Niger in general and in the Maradi region in particular, the management of space and natural resources leads to problems for agricultural and livestock farms. This study was conducted in the Maradi region in order to characterize the agriculture-livestock-environment integration system at the farm level in the Maradi region along the gradient of North (Dakoro), Center (Guidan Roumdji), South (Madarounfa). The methodology used to achieve this objective consisted of surveys of 300 households in the Maradi region, which were then analysed using Hierarchical Ascending Classification (HAC) and Principal Component Analysis (PCA). The results allowed us to distinguish three groups of farm sizes. Group 1 farms are characterized by large farms with an age greater than 41 years, a total cultivated area greater than 1 ha, and a large number of livestock greater than 3 UTF. These farmers are more represented in Dakoro (57%) and Guidan Roumdji (38%) and are more involved in Agriculture-Livestock-Environment than the other groups. As for group 2 farms, they are more numerous than group 1 farms in Guidan Roumdji (49%) and Madarounfa (49%). These farms have a cultivated area > 3 ha and a number of dependents between 5 and 14 peoples. The farms in group 3 are the least old and less numerous than those in groups 1 and 2, with very low values in Dakoro. This study categorized farmers in the Maradi region into three groups according to age, field area, household size and number of animals. It shows that agriculture-livestock-environment integration is practised by all the farms surveyed, but at different levels. Finally, particular attention was paid to the contribution of this agriculture-livestock-environment integration to improving soil fertility, household income and food and nutritional security.